Brain death Scientific aspects and ethical issues - Manni, Corrado (Medicina e Morale, 2024)
If there is so much talk of 'brain death' today, it is mainly due to two main reasons: the continuing advances in resuscitation and organ transplants, which have drawn everyone's attention to the meaning of the term 'brain death' in recent years.